Business sustainability: the role of msme innovation capabilities in Sukabumi - Ce Gunawan; Intan Rike Febriyanti (Institute of Computer Science (IOCS), 2023)
MSMEs have an important role in increasing economic growth. The aim of this research is to determine the influence of innovation capability on the business sustainability of MSMEs in Sukabumi City. The research method used is a quantitative research method using multiple linear regression analysis. The unit of analysis in this research is MSME actors in Sukabumi. The number of samples in this research was 379 MSME actors determined using the Isaac & Michael formula. The sampling technique uses a random sampling method. Data was collected using a questionnaire that had been tested for validity and reliability. Data analysis using SPSS. The research results show that innovation capabilities have a significant impact on the business sustainability of Sukabumi MSMEs